Durrington walls and the Stonehenge Hidden Landscape Project 2010–2016. Issue 3 (15th August 2018) - Gaffney, Vincent; Neubauer, Wolfgang; Garwood, Paul; Gaffney, Christopher; Löcker, Klaus; Bates, Richard; De Smedt, Phillipe; Baldwin, Eamonn; Chapman, Henry; Hinterleitner, Alois; Wallner, Mario; Nau, Erich; et al.
Abstract: Since 2010 the Stonehenge Hidden Landscapes Project (SHLP) has undertaken extensive archaeological prospection across much of the landscape surrounding Stonehenge. These remote sensing and geophysical surveys have revealed a significant number of new sites and landscape features whilst providing new information on many previously known monuments. The project goal to integrate multimethod mapping over large areas of the landscape has also provided opportunities to re‐interpret the landscape context of individual monuments and, in the case of the major henge at Durrington Walls, to generate novel insights into the structure and sequence of a monument which has attracted considerable research attention over many decades. This article outlines the recent work of the SHLP and the results of the survey at Durrington Walls that shed new light on this enigmatic monument including a site 'hidden' within the monument.